Precipitação e movimentos de massa: contribuição à emissão de alerta nos municípios de Coimbra - Portugal e Campinas (SP) - Brasil - Pellegrina, Geórgia Jorge [UNESP] (2015)
This work analyzes natural disasters (geological, meteorological, hidrological, climatological and biological) which occurred in various parts of the world, related to number of deaths. In various parts of the world, the floods (hidrological disasters) followed by the mass movement (geological disasters) are the disasters which caused great damage with fatal victims triggered by precipitation, it is the case of some regions of Brazil and in Portugal. For warning issuance, it was necessary to establish the relationships between precipitation and mass movement for the studied locations, Coimbra - PT and Campinas - SP/Brazil.It was important to distinguish the effects of rain distribution in time: long-lasting rain, low rain and/or high intensity rain, as well as the behavior of rain over a certain period. The study took into account climate variability, associated with ENSO and NAO, in the behavior of rainfall respectively in Campinas-SP and Coimbra-PT, and weather systems operating in each of the studied regions. The tests results showed that ENSO has not consistently changed precipitation volumes in Campinas, while NAO has contributed to the high volumes of precipitation in the region of Coimbra. The relationship between rainfall and mass movements for the municipalities of Campinas and Coimbra was established by criteria of accumulated volumes of precipitation in 3,5 and 10 days prior to the events at meteorological stations, and 24, 48 and 72 hours prior to the events by use of weather radar IPMET only for Campinas. Thus, it was possible to establish criteria for alert issued by monitoring the rain gauge precipitation and by accumulated precipitation products generated by the weather radar for the city of Campinas. The weather radar proved to be an important tool for the mass movement risk management due to its high spatial and temporal resolution, besides monitoring precipitation, its intensity and its displacement